(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The article discusses the role and place of statehood in the dynamics of its development among the research circles of various scientific theorists. A new concept of statehood is also revealed, which is characterized more widely than the classical concept of statehood within one country, limited by its sovereignty. In addition, the author compares the statehood of various countries and identifies the features of institutional management. The author comes to the conclusion that modern statehood in the context of the formation of political institutions has undergone significant changes from its classical understanding. and statehood should be interpreted much broader to include various international organizations.